The Importance of Information Quality Aspects in the Web-based Information Systems Development in Web-Consulting Organisations - Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing; Sulong, Muhammad Suhaizan (2013)
Information quality issues are critical for various information systems including on the web. Indeed, many research studies have focused on assessing the quality of web information but this study is significant as one of a very few to examine the information quality in web development environments. The purpose of this study is to present the outcomes of case studies conducted in seven web-consulting organisations that focus on building web-based information systems for their clients, which is then to demonstrate the importance of employing information quality in their web development methodology. The quality of information during the web development was perceived as poor and below expectations by the web development team. This paper finds that high information quality across web development processes will be able to improve the development of web-based information systems and thus, many web-consulting organisations should employ a set of information quality strategies to ensure an appropriate level of quality for their web development methodology.